Phytochemical Composition and Biological Activity of Berries and Leaves from Four Romanian Sea Buckthorn (Hippophae Rhamnoides L.) Varieties - Adriana Criste; Adriana Cristina Urcan; Andrea Bunea; Flavia Roxana Pripon Furtuna; Neli Kinga Olah; Robert H. Madden; Nicolae Corcionivoschi (Molecules, 2020)
Hippophae rhamnoides L. is an important source of natural antioxidant and antimicrobial agents. Phytochemical compounds, antioxidant and antibacterial properties of berries, and leaf extracts from four Romanian sea buckthorn cultivars were investigated. Large differences in the content of total polyphenols and flavonoids between the varieties were observed. HPLC analysis of the polyphenolic compounds showed greater differences in content in leaves than in berries. This study confirmed that sea buckthorn leaves and berries are a rich source of phenolic compounds, especially quercetin derivatives and hydrocinnamic acid derivatives. Five carotenoid compounds were identified in the berries: lutein, zeaxanthin, β-cryptoxanthin, cis-β-carotene, and β-carotene. From the results obtained in this study, it can be stated that the varieties whose berries yielded the highest quantities of polyphenols, flavonoids, and antioxidant activity, can be ranked as follows: SF6 > Golden Abundant > Carmen > Colosal, and for leaf extracts the ranked order is SF6 > Golden Abundant > Colosal > Carmen. A strong correlation between the total flavonoid yield and antioxidant activity (r = 0.96), was observed. All extracts showed antibacterial activity against S. aureus, B. cereus, and P. aeruginosa, however extracts from berries were less potent than extracts from leaves.